Prognostic Value of Preoperative NLR and Vascular Reconstructive Technology in Patients With Pancreatic Cancer of Portal System Invasion: A Real World Study - Zhou, Lin; Wang, Jing; Zhang, Xin-xue; Lyu, Shao-cheng; Pan, Li-chao; Du, Guo-sheng; Lang, Ren; He, Qiang (Frontiers in Oncology, 2021)
The purpose was aimed to establish a simple computational model to predict tumor prognosis by combining NLR and biomarkers of oncological characteristics in patients undergoing vascular reconstructive radical resection of PDAC. The enrolled patients was divided into high or low NLR group with the cutoff value determined by the ROC curve. Different vascular anastomoses were selected according to the Chaoyang classification of PDAC. Survival rates were calculated using the Kaplan-Meier and evaluated with the log-rank test. Cox risk regression model was used to analyze the independent risk factors for prognostic survival. The optimal cut-off value of NRL was correlated with the differenitation, tumor size, TNM stage and distant metastasis of advanced PDAC. A curative resection with vascular reconstructive of advanced PDAC according to Chaoyang classification can obviously improve the survival benefits. Cox proportional hazards demonstrated higher evaluated NLR, incisal margin R1 and lymphatic metastasis were the independent risk predictor for prognosis with the HR > 2, meanwhile, age beyond 55, TNM stage of III-IV or Tumor size > 4cm were also the obvious independent risk predictor for prognosis with the HR ≤ 2. The advanced PADC patients marked of RS group ( 3 < RS ≤ 6) showed no more than 24 months of survival time according to RS model based on the six independent risk predictors. Vascular reconstructive in radical resection of advanced PDAC improved survival benefits, higher elevated NLR (>2.90) was a negative predictor of DFS and OS in those patients accompaning portal system invasion.